The Hippo Signaling Core Components YAP and TAZ as New Prognostic Factors in Lung Cancer - Jiang, Yu; Xie, Wen-Jing; Chen, Rong-Wei; You, Wei-Wei; Ye, Wei-Lin; Chen, Hong; Chen, Wen-Xu; Xu, Jian-Ping (Frontiers in Surgery, 2022)
Background The Hippo pathway is an essential signaling cascade that regulates cell and organ growth. However, there is no consensus about (i) the expression levels of the Hippo signaling core components yes-associated protein (YAP) and transcriptional co-activator with PDZ-binding motif (TAZ) in lung cancer, especially in small cell lung cancer (SCLC), or (ii) their association with the prognosis of patients with SCLC. Methods We screened relevant articles and identified eligible studies in the PubMed, EMBASE, COCHRANE, and WanFang databases. A combined analysis was performed to investigate (i) the expression levels of the major effectors, YAP and TAZ, in lung cancer and its subsets and (ii) their prognostic role in lung cancer, especially in SCLC. Results In total, 6 studies related to TAZ and 13 studies concerning YAP were enrolled in this meta-analysis. We found that high TAZ expression was significantly associated with poor overall survival (OS) of patients with non-small cell lung cancer (NSCLC) in the overall population [Ph < 0.001, crude hazard ratio (HR) = 1.629, 95% CI = 1.199–2.214 for TAZ expression; Ph = 0.029, adjusted HR = 2.127, 95% CI = 1.307–3.460 for TAZ], the Caucasian population (Ph = 0.043, crude HR = 1.233, 95% CI = 1.030–1.477 for TAZ expression), and the Asian population (Ph = 0.551, adjusted HR = 2.676, 95% CI = 1.798–3.982 for TAZ). Moreover, there was a significant negative association between YAP expression and an unsatisfactory survival of patients with lung cancer (Ph = 0.327, crude HR = 1.652, 95% CI = 1.211–2.253 for YAP expression) and patients with NSCLC [disease-free survival (DFS): Ph = 0.693, crude HR = 2.562, 95% CI = 1.876–3.499 for YAP expression; Ph = 0.920, crude HR = 2.617, 95% CI = 1.690–4.052 for YAP-mRNA; OS: Ph = 0.878, crude HR = 1.777, 95% CI = 1.233–2.562 for YAP expression], especially in the Asian population (DFS: Ph = 0.414, crude HR = 2.515, 95% CI = 1.755–3.063; OS: Ph = 0.712, crude HR = 1.772, 95% CI = 1.214–2.587). However, no association was observed in the multivariate combined analysis. High YAP expression was significantly associated with short OS of patients with SCLC in our combined multivariate analysis in the Asian population (Ph = 0.289, crude HR = 4.482, 95% CI = 2.182–9.209), but not with crude data (Ph = 0.033, crude HR = 1.654, 95% CI = 0.434–6.300). Conclusion The Hippo pathway is involved in carcinogenesis and progression of NSCLC and SCLC, and high expression levels of YAP and TAZ are independent and novel prognostic factors for lung cancer.